2001
DOI: 10.1111/j.1533-8525.2001.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Inequality in Homeownership and Housing Equity

Abstract: Wealth inequality, particularly in housing, has received increased attention in recent years for its importance to racial and ethnic stratification. Yet, while we know a fair amount about black‐white wealth inequality, many questions remain regarding sources of Hispanic asset inequality. This article addresses this gap by examining racial and ethnic inequality in homeownership and housing equity among the pre‐retirement population. Results support a stratification perspective of inequality for both blacks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(17 citation statements)
references
References 27 publications
(16 reference statements)
1
16
0
Order By: Relevance
“…The same is true for mortgage and housing characteristics for blacks and Hispanics. These findings are consistent with Flippen's (2001a) study of home equity among preretirement-age whites, blacks, and Hispanics, as well as with considerable evidence that nonwhites are widely discriminated against in the housing market in ways that limit their access to the most-favorable neighborhoods and housing (Alba and Logan 1992;Alba et al 2000a;Flippen 2001b;Logan and Alba 1993;Massey and Denton 1993;Rosenbaum and Friedman 2001 ;Ross and Yinger 2002;Yinger 1995). Such discrimination (e.g., providing less information, steering to more heavily minority areas, showing smaller, lower-quality, or lower-value homes) should mute the influence of family and market factors on housing equity, as we found here.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The same is true for mortgage and housing characteristics for blacks and Hispanics. These findings are consistent with Flippen's (2001a) study of home equity among preretirement-age whites, blacks, and Hispanics, as well as with considerable evidence that nonwhites are widely discriminated against in the housing market in ways that limit their access to the most-favorable neighborhoods and housing (Alba and Logan 1992;Alba et al 2000a;Flippen 2001b;Logan and Alba 1993;Massey and Denton 1993;Rosenbaum and Friedman 2001 ;Ross and Yinger 2002;Yinger 1995). Such discrimination (e.g., providing less information, steering to more heavily minority areas, showing smaller, lower-quality, or lower-value homes) should mute the influence of family and market factors on housing equity, as we found here.…”
Section: Discussionsupporting
confidence: 83%
“…However, many studies have also shown that black and Hispanic households are dealt with less favorably than majority whites at each stage of the process, from locating to acquiring to financing housing (Farley 1996;Massey and Denton 1993;Ross and Yinger 2002;Turner 1992;Yinger 1995Yinger , 1997. Such differential treatment should reduce minorities' accumulation of home equity compared with whites' in that blacks and Hispanics find it more difficult to purchase homes and to do so with favorable mortgage terms in areas with high values and levels of appreciation (Bradford 2002;Flippen 2001aFlippen , 2001bKrivo 1995;Long and Caudill 1992;Munnell et al 1996;Ross and Yinger 2002;Turner 1992;Yinger 1995). …”
Section: Housing and Wealth Inequality: Racial-ethnic Differences In mentioning
confidence: 99%
See 3 more Smart Citations